Intrinsic lithium storage mechanisms and superior electrochemical behaviors of monodispersed hierarchical CoCO3 sub-microspheroids as a competitive anode towards Li-ion batteries. (1st June 2019) - Zhao, Zhiwei; Wang, Zhengluo; Denis, Dienguila Kionga; Sun, Xuan; Zhang, Jinyang; Hou, Linrui; Zhang, Xiaogang; Yuan, Changzhou
Abstract: Recently, CoCO3 is attracting extensive interests as a promising anode for Li-ion batteries (LIBs) thanks to its large capacities and simple synthesis. However, its modest electrochemical behaviors and ambiguous lithium storage mechanisms still need to be well addressed. Herein, we devise a scalable bottom-up solvothermal methodology to fabricate monodispersed pinecone-like CoCO3 sub-microspheroids constructed with nanosheet subunits. When evaluated as appealing anode for LIBs, the resultant CoCO3 anode exhibits high initial Coulombic efficiency of ∼75.2%, and large reversible capacity of ∼1008 mAh g −1 at a rate of 200 mA g −1, and even ∼663 mAh g −1 at 2 A g −1, benefiting its hierarchical micro-/nanostructures. Besides, the enhanced interfacial charge-storage capability of the CoCO3 sub-microspheroids with cycling accounts for the long-duration capacity retention of ∼138% over 500 consecutive cycles. More significantly, comprehensive lithium storage mechanism of the CoCO3, involving conventional conversion reactions, reversible redox reaction of low-valence C/C(IV), and debut observation of reversible Co(II)/Co(III) transition, is proposed with in-situ and ex-situ physicochemical and electrochemical investigations. Furthermore, a CoCO3 //LiNi0.8 Co0.15 Al0.05 O2 full battery is assembled and delivers prominent electrochemical properties, hugely highlighting the enormous potential of our CoCO3 sub-microspheroids in next-generation LIBs as competitive anodes. Graphical abstract: Monodispersed hierarchical CoCO3 sub-microspheroids were scale-up fabricated and displayed superior electrochemical behaviors. More significantly, intrinsic lithium storage mechanisms were proposed as a competitive anode towards Li-ion batteries.Image 1 Highlights: A solvothermal method was devised to fabricate CoCO3 sub-microspheroids. The monodispersed sub-microspheroids were constructed with nanosheets. The resultant CoCO3 anode exhibited superior Li-storage behaviors. The comprehensive lithium-storage mechanism of CoCO3 was proposed. A CoCO3 -based full device with prominent Li-storage properties was assembled.